Evaluation of microfiltration in restorations with resin Class I. - Cáceres Díaz, Laura María (2021)
Objective: To compare the depth of microfiltration in resin restorations in Class I cavities, varying the restoration method and the adhesive system. Material and Methods: an ex vivo experimental study was carried out, in which 128 molars without morphological alterations in the coronary structure were included, in which cavities were carved in the occlusal face in a standardized way (4x4x3mm) and later randomly distributed in two groups according to the adhesive system applied (Group I, acid etching prior to the adhesive; Group II, self-etchingadhesive), each Group being subdivided into two subgroups according to the restoration method, A: composite resin; B: Flowable resin base, composite resin restoration and surface sealer. All trial bodies were sealed at the apex and on the entire external surface with two layers of nail polish up to 1 mm from the tooth-restoration interface, thermocycled between 5 ° C and 55 ° C, immersed in methylene blue at 2 % for 24 hours and cut transversely in the palatal / lingual vestibule direction to measure in millimeters. Results: The data were statistically analyzed with IBM SPSS stadicts version 2.0, applying double classification ANOVA; a statistically significant difference (p <0.05) was observed between the subgroups according to the restoration method. Conclusions: the use of base and surface sealer in combination with the composite resin restoration decreased microfiltration by applying both the adhesive system with previous acid etching and the self-etched adhesive system, while the highest microleakage was obtained with composite resin (without base or sealer surface) and the use of the self-etching adhesive system.